Strengthening the Competencies of Islamic Religious Education Teachers in Facing the Era of Society 5.0 - Qur'ani, Muhammad Nuzulul; Zakiyah, Nur; Basri, Hasan; Zakaria, Abd Razak (STAI Publisistik Thawalib Jakarta, 2025)
Low technological mastery, minimal ongoing training, and limited facilities require Islamic Religious Education teachers at State Junior High School 24 Medan to have religious, technological, and learning method competencies that are relevant in the era of society 5.0. This study aims to explore information related to strengthening the competence of Islamic Religious Education teachers in facing the era of society 5.0 at State Junior High School 24 Medan. This study uses a qualitative research approach, using the sociology of education. Data collection techniques using interviews, observation and documentation. Data validity checks using triangulation. Meanwhile, the data analysis technique follows Miles and Huberman which goes through the stages of data reduction, data presentation, drawing conclusions, and verification. The results of this study indicate that the efforts of Islamic Religious Education teachers in improving competency strengthening in the era of society 5.0 at State Junior High School 24 Medan can be done through participating in the teacher professional education programme, joining a teacher organisation, increasing collaboration and cooperation, and utilising technology media. The obstacles faced by Islamic Religious Education teachers in implementing competencies in the era of society 5.0 include lack of mastery in the use of technological tools, inadequate school facilities, and lack of full support from parents of students.